Interactive GeoGebra media embedded in student worksheets: a design approach to foster mathematical engagement in 3D Geometry - Sugiarni, Rani; Aulia, Pitri; Suryadini, Novi; Bonyah, Ebenezer; Olivero-Acuña, Ronaldo Rafael (Universitas Terbuka, 2025)
Geometry, particularly three-dimensional (3D) geometry, is often perceived by students as abstract and difficult, resulting in low engagement and interest. Addressing this issue, the present study aimed to design interactive learning media using GeoGebra integrated with Student Worksheets to enhance students’ interest in learning 3D geometry. The research employed a Research and Development (R&D) methodology, encompassing the stages of needs analysis, design, development, implementation, and evaluation. The participants were 30 students from a public high school in Cianjur, Indonesia, who were involved in mathematics instruction on 3D geometry topics. Data were collected through student response questionnaires assessing the usability and effectiveness of the developed media. The findings indicate that the GeoGebra-based Student Worksheet media met validity and practicality criteria, with students responding positively to its use. They reported that the interactive features of the media facilitated better conceptual visualization and significantly increased their interest in learning. Furthermore, implementation strategies—such as teacher demonstrations, collaborative group work, and guided class discussions—proved effective in mitigating the abstractness of 3D geometry. This research contributes to the growing body of literature on technology-enhanced mathematics instruction by offering a practical and engaging learning solution. The integration of GeoGebra-based Student Worksheets is therefore recommended as an effective pedagogical tool to foster students’ mathematical interest and conceptual understanding, especially in abstract topics like three-dimensional geometry.